2015
DOI: 10.1208/s12248-015-9850-5
|View full text |Cite
|
Sign up to set email alerts
|

Neonatal Immune Tolerance Induction to Allow Long-Term Studies With an Immunogenic Therapeutic Monoclonal Antibody in Mice

Abstract: Abstract. The purpose of this study is to test the feasibility of neonatal immune tolerance induction in mice to enable long-term pharmacokinetic studies with immunogenic therapeutic monoclonal antibodies (mAb). Neonatal immune tolerance was induced by transfer of a mAb to neonatal mice via colostrum from nursing mother mice treated with two subcutaneous doses of a tolerogen starting within the first 24 h after delivery. Adalimumab and efalizumab were administered as tolerogens at various dose levels. Toleranc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
2
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 26 publications
2
2
0
Order By: Relevance
“…The drugs with immunosuppressive effect like methotrexate reduce the production of anti-adalimumab antibodies by suppressing the immune response ( Ducourau et al, 2020 ). In this study, the production of anti-adalimumab antibodies was observed in rats with CIA under the continuous treatment of adalimumab, which was consistent with the results of other study ( Piccand et al, 2016 ). More interestingly, a comparative level of anti-adalimumab antibodies was also observed between the rats in the adalimumab-treated and delanzomib + adalimumab-treated groups, suggesting that delanzomib less affected the expression of anti-adalimumab antibodies.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…The drugs with immunosuppressive effect like methotrexate reduce the production of anti-adalimumab antibodies by suppressing the immune response ( Ducourau et al, 2020 ). In this study, the production of anti-adalimumab antibodies was observed in rats with CIA under the continuous treatment of adalimumab, which was consistent with the results of other study ( Piccand et al, 2016 ). More interestingly, a comparative level of anti-adalimumab antibodies was also observed between the rats in the adalimumab-treated and delanzomib + adalimumab-treated groups, suggesting that delanzomib less affected the expression of anti-adalimumab antibodies.…”
Section: Discussionsupporting
confidence: 93%
“…The formation of mAb-ADA immune complexes can accelerate the clearance of mAbs via the activation of complement and increased uptake by phagocytic cells and red blood cells ( Schellekens, 2002 ). Although adalimumab is humanized mAbs, adalimumab can still cause immune response to produce anti-adalimumab antibodies in rats due to its immunogenicity for rats ( Piccand et al, 2016 ). The drugs with immunosuppressive effect like methotrexate reduce the production of anti-adalimumab antibodies by suppressing the immune response ( Ducourau et al, 2020 ).…”
Section: Discussionmentioning
confidence: 99%
“…This can most likely be explained by increased aTNFα clearance by the formed ADAs. 1,9,19,40 –46 Additionally, there was an unexplainable high incidence and concentration of ADAs in the vehicle group at week 13 in the dose regimen study as also observed previously. 46 The ADAs might have formed in response to exposure to low levels of aTNFα present at the animal facility 46 ; however, these animals in the present study had no measured aTNFα exposure or increased IC formation or deposition, apart from a low level of cCIC, C3d, and mIgM in IHC staining as incidentally observed in vehicle-administered animals.…”
Section: Discussionsupporting
confidence: 75%
“…Heterozygous 6-week-old Tg197 mice were gender-balanced and assigned to two groups for the pharmacokinetic study of adalimumab and ozoralizumab (35)(36)(37). The animals in the adalimumab group (n = 4) and the ozoralizumab group (n = 4) were subcutaneously injected with adalimumab or ozoralizumab both at 1 mg/kg.…”
Section: Pharmacokinetic Studymentioning
confidence: 99%